Assessment of the Slovak and Latvian Agriculture from the Point of Plant Production - Hemmali Nagmy; Patrik Rovny; Aleksejs Zuravlovs (Polityki Europejskie, Finanse i Marketing)
Agriculture as one of major industries of the national economy is closely connected with the development of the whole country, especially rural regions and food production. Therefore it should be viewed as an important factor of rural development and economic stability of the whole country. The main aim of article is to compare the position of plant production and agriculture in two EU countries: Slovakia and Latvia. Realization of the mentioned objective required the research within the period of the years 2009-2010. We used basic organizational and economic relations and numeric calculations while analyzing and forming the theoretical and practical solutions. According to crop production between Slovakia and Latvia outlines some similarities, the situation was reversed and crops production for most commodities has fallen, particularly in case of cereals, but some separate crops have the various tend. For example in Slovakia case crop production rise of legumes and sugar beet, parallel in Latvia case crop production increase rapidly of buckwheat and rape. In consequence it draws differences in crop production priorities which depends from a large number of different circumstances between two described countries.